2020
DOI: 10.1186/s40364-020-00207-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet biomarkers in inflammatory response

Abstract: Beyond hemostasis, thrombosis and wound healing, it is becoming increasingly clear that platelets play an integral role in inflammatory response and immune regulation. Platelets recognize pathogenic microorganisms and secrete various immunoregulatory cytokines and chemokines, thus facilitating a variety of immune effects and regulatory functions. In this review, we discuss recent advances in signaling of platelet activation-related biomarkers in inflammatory settings and application prospects to apply for dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 95 publications
(136 reference statements)
1
70
1
Order By: Relevance
“…Surprisingly, although the chain length of polyP may be a matter for further investigation, it has been reported that polyanions like polyP can form a complex with PF4 and that this complex activates platelets as does the PF4-heparin complex. 31,34 Platelets also release anti-inflammatory cytokines, such as IL-4 and IL-10, upon activation, 1 and thus platelet-rich plasma (PRP) has been clinically utilized as an antiinflammatory agent or a pain-releasing agent. 35 At present, it is difficult to predict the risk of PF4-polyP complex-induced thrombosis by the "autocrine" loop or by exposure to bacterial polyP after vaccination.…”
Section: Possible Platelet Activation and Thrombosis By Polypmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, although the chain length of polyP may be a matter for further investigation, it has been reported that polyanions like polyP can form a complex with PF4 and that this complex activates platelets as does the PF4-heparin complex. 31,34 Platelets also release anti-inflammatory cytokines, such as IL-4 and IL-10, upon activation, 1 and thus platelet-rich plasma (PRP) has been clinically utilized as an antiinflammatory agent or a pain-releasing agent. 35 At present, it is difficult to predict the risk of PF4-polyP complex-induced thrombosis by the "autocrine" loop or by exposure to bacterial polyP after vaccination.…”
Section: Possible Platelet Activation and Thrombosis By Polypmentioning
confidence: 99%
“…Upon infection, platelets first bind to infectious pathogens, such as bacteria and viruses, secrete various immunoregulatory cytokines, and express receptors for mediating various immune effects and regulatory functions. 1 Platelets regulate macrophage functions, regulatory T cells, and secrete pro-resolving mediators. 2 However, their regulatory functions are not simple: both proinflammatory and anti-inflammatory regulations are included and modulated by the degree and the phase of injury and inflammation (for more details, see "4 Discussion section").…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are recruited at the site of inflammation and they have the ability to release multiple proinflammatory cytokines which further recruit platelets. [3][4][5] respiratory distress and even convulsions and unconsciousness.…”
Section: Introductionmentioning
confidence: 99%
“…Mean platelet volume (MPV) has been determined as marker of platelet activation in inflammatory process. 4,5 Changes in MPV will directly influence platelet distribution width (PDW) which indicate variation of platelet size. MPV and PDW value are readily available as platelet parameter in complete blood count, and this examination is routinely done in patients with COVID-19.…”
mentioning
confidence: 99%